The Effectiveness of Premarital Counseling Service on the Harmony of Marriage in Family Resilience - Samad, Duski; remiswal, remiswal; Kenedi, Gusril; Mustqim, Mujahidil (AT-TALIM, 2016)
The hypothesis of preliminary research stated that the high rate of divorcement in West Sumatera was caused by the weakness of the role and function of Badan Penasihatan Pembinaan dan Pelestarian Perkawinan (Board of Marriage Advisory and Preservation) or BP4 in every district in providing premarital counseling service, thus prospective couples have not enough marital knowledge to work on their households. The aim of the research is to reveal the effectiveness of premarital counseling service on the harmony of marriage in realizing family resilience in West Sumatera.The research applied the mixed research method by using sequential explanatory design model. The research object included first, the prospective husbands/wives who had been provided premarital counseling service by the BP4 in West Sumatera, and second, the coaches and counselors of the BP4 premarital counseling service in West Sumatera.The results showed that, first, the effectiveness of premarital counseling service on the harmony of marriage reached as high as 3% in Pariaman, and as low as 0.1% in Pesisir Selatan; second, the effectiveness of premarital counseling service on family resilience had as high as 4.5% in Lima Puluh Kota district, and as low as 0.1 % in Pesisir Selatan; and third, the role of the BP4 in West Sumatera was, in fact, very low.